Australia : Selected Issues. (IMF Staff Country Reports; Country Report, 2020)
This Selected Issues paper investigates the drivers of business investment in Australia, focusing on the non-mining sectors. The paper also identifies aggregate-level drivers for non-mining business investment by looking at long-term trends. It delves into firm-level investment behavior and assesses the role of credit availability and uncertainty in different types of firms. Long-term empirical and simulation-based analyses suggest that global factors such as rising policy uncertainty and weaker commodity prices have been key drivers of the slowdown, while in the short term, a renewed escalation in US-China trade tensions could spill over to investment and growth in Australia. Yet, domestic factors are also at play, including domestic policy uncertainty and financial constraints, especially for smaller and younger firms. The pace of product market reforms can also impact business investment. Australia can promote business investment by reducing domestic policy uncertainty, easing credit constraints for small- and medium-sized enterprises, incentivizing research and development, and continuing with product market and tax reforms.